2014
DOI: 10.1039/c3cc47521b
|View full text |Cite
|
Sign up to set email alerts
|

Eutectics as improved pharmaceutical materials: design, properties and characterization

Abstract: Eutectics are a long known class of multi-component solids with important and useful applications in daily life. In comparison to other multi-component crystalline solids, such as salts, solid solutions, molecular complexes and cocrystals, eutectics are less studied in terms of molecular structure organization and bonding interactions. Classically, a eutectic is defined based on its low melting point compared to the individual components. In this article, we attempt to define eutectics not just based on therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
303
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 240 publications
(311 citation statements)
references
References 136 publications
8
303
0
Order By: Relevance
“…For this kind of drugs, besides cocrystals, binary eutectic mixtures, for instance, are also relevant [23][24][25][26] due to their increased surface area and the potential for increasing dissolution rate. Therefore, the establishment of the binary solid-liquid phase diagrams of the API and the potential co-former is of considerable interest as it gives comprehensive information of the solid binary mixtures behavior.…”
Section: Introductionmentioning
confidence: 99%
“…For this kind of drugs, besides cocrystals, binary eutectic mixtures, for instance, are also relevant [23][24][25][26] due to their increased surface area and the potential for increasing dissolution rate. Therefore, the establishment of the binary solid-liquid phase diagrams of the API and the potential co-former is of considerable interest as it gives comprehensive information of the solid binary mixtures behavior.…”
Section: Introductionmentioning
confidence: 99%
“…A solid solution is a variable stoichiometry multicomponent crystalline solid formed by substitutional incorporation of a component in the lattice of another component Multicomponent crystals such as solvates, hydrates, salts, and cocrystals can also exist in polymorphic forms (Adapted from Ref. [8] with permission from The Royal Society of Chemistry) [7]. Eutectics are conglomerates of solid solutions or conglomerates of lattice structures of different materials [8].…”
Section: Different Solid Formsmentioning
confidence: 99%
“…[8] with permission from The Royal Society of Chemistry) [7]. Eutectics are conglomerates of solid solutions or conglomerates of lattice structures of different materials [8]. Amorphous materials are distinct from the abovementioned solids, which lack long-range molecular order and relatively high energy materials compared to their crystalline counterparts [9].…”
Section: Different Solid Formsmentioning
confidence: 99%
“…5 Cocrystallization studies serve as an important methodology to probe the physical and supramolecular compatibility of a given combination, particularly multi-nutrient/drug combinations, and achieve an optimal formulation for the combination. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] Friščić et al emphasized the biological and pharmaceutical significance of cocrystallization through their studies on steroid hormones. 20,21 In their recent review, Sinha et al 6 noted that in spite of the importance of cocrystallization studies on vitamins, they were found to be least explored.…”
Section: Introductionmentioning
confidence: 99%